Komunikasi Digital Membangun Loyalitas Pelanggan Somethinc dalam Shopee - Tanuwijaya, Rio; Sari, Wulan Purnama (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Digital communication has become an important component of customer engagement strategies in e-commerce platforms. This study analyzes how digital communication contributes to the development of customer loyalty toward the Somethinc brand on Shopee. The theoretical framework covers interactivity, information quality, responsiveness, and participation as indicators of digital communication. A quantitative method was applied through a survey of one hundred respondents selected using purposive sampling. Data analysis includes validity testing, reliability testing, normality testing, Pearson correlation, simple linear regression, and the t test using SPSS software. Results show that digital communication has a positive and significant effect on customer loyalty. The coefficient of determination indicates that digital communication contributes 5.9 percent to loyalty, while the remaining percentage is influenced by other external variables. The regression coefficient confirms that each unit increase in digital communication contributes to an increase in customer loyalty. These findings emphasize the significance of well managed digital communication in supporting brand consistency and sustaining customer loyalty in competitive e-commerce environments. Komunikasi digital menjadi bagian penting dalam mengelola hubungan antara merek dan pelanggan pada platform e-commerce. Penelitian ini menganalisis kontribusi komunikasi digital terhadap pembentukan loyalitas pelanggan Somethinc di Shopee. Kerangka teori mencakup interaktivitas, kualitas informasi, responsivitas, dan partisipasi sebagai indikator komunikasi digital. Penelitian menggunakan metode kuantitatif dengan survei terhadap seratus responden melalui teknik purposive sampling. Analisis data meliputi uji validitas, reliabilitas, normalitas, korelasi Pearson, regresi linear sederhana, serta uji t dengan bantuan SPSS. Hasil menunjukkan bahwa komunikasi digital berpengaruh positif dan signifikan terhadap loyalitas pelanggan. Koefisien determinasi menunjukkan bahwa komunikasi digital memberikan kontribusi sebesar 5.9 persen terhadap loyalitas, sedangkan persentase lainnya dipengaruhi oleh faktor eksternal. Koefisien regresi mengonfirmasi bahwa peningkatan komunikasi digital berhubungan dengan peningkatan loyalitas pelanggan. Temuan ini menegaskan pentingnya pengelolaan komunikasi digital sebagai strategi untuk mempertahankan loyalitas di tengah persaingan e-commerce.